Expressão do gene VEGFA em tecido adiposo subcutâneo e visceral de mulheres em obesidade grau III - Silva, Fabiano Honorato Pereira e (2013)
Obesity is a chronic and multifactorial disease resulting from a complex interaction of genetic and environmental risk. Despite efforts to develop actions to prevent and control, the prevalence of obesity continues to grow around the world. This disease is characterized by excess of body fat accumulation in adipose tissue deposits, subcutaneous (SAT) and visceral (VAT). Adipose tissue is highly vascularized and has intense angiogenic activity. For its expansion is required to occur the development of blood vessels from pre-existing vessels. The VEGFA gene is a important pro-angiogenic factors and acts promoting vasopermeability, migration and proliferation of endothelial cells. The objectives of this study were to observe the differences in the expression of VEGFA in SAT and VAT. The objectives of this study were to observe the differences in the expression of VEGFA in SAT and VAT. In addition, we also analyzed associations with clinical parameters and gene expression of adiponectin, a anti-inflammatory adipokine associated with protection against changes in glucose tolerance. In this study was performed, using the technique of quantitative PCR in real-time, the analysis of VEGFA gene expression in SAT and VAT of 33 female patients with morbid obesity (BMI ≥ 40). The sample was divided into two groups: a group with abnormal glucose tolerance (n = 9) and a group without these abnormalities (n = 19). In the total sample, the VEGFA was expressed similarly in both deposits. However, women with abnormal glucose tolerance had reduced expression of VEGFA in VAT. Moreover, in SAT the age was negatively correlated to this gene and in VAT the VEGFA gene was positively associated with overweight and negatively associated with total cholesterol and HDL. Furthermore, consistent positive correlations were observed between VEGFA and adiponectin, both SAT and in VAT. These results are important because they help to clarify the involvement and activity of VEGFA in adipose tissue